Controlling the Modal Confinement in Silicon Nanophotonic Waveguides through Dual‐Metamaterial Engineering. Issue 3 (5th January 2023) - Dinh, Thi Thuy Duong; Le Roux, Xavier; Zhang, Jianhao; Montesinos‐Ballester, Miguel; Lafforgue, Christian; Benedikovic, Daniel; Cheben, Pavel; Cassan, Eric; Marris‐Morini, Delphine; Vivien, Laurent; Alonso‐Ramos, Carlos
Abstract: Flexible control of the modal confinement in silicon photonic waveguides is an appealing feature for many applications, including sensing and hybrid integration of active materials. In most cases, strip waveguides are the preferred solution to maximize the light interaction with the waveguide surroundings. However, the only two degrees of freedom in Si strip waveguides are the width and thickness, resulting in limited flexibility in evanescent field control. Here, a new strategy that exploits metamaterial engineering of the waveguide core and cladding is proposed and demonstrated to control the index contrast in the vertical and horizontal directions, independently. The proposed dual‐material geometry yields a substantially increased calculated bulk sensitivity in the air (0.35 RIU [refractive index unit]/RIU) compared to the best case scenario for a strip waveguide (0.3 RIU/RIU). To experimentally demonstrate the potential of this approach, dual‐metamaterial ring resonators operating with the transverse‐magnetic polarized mode in 220‐nm‐thick waveguides with air as upper‐cladding are implemented. Micro‐ring resonators implemented with strip and dual‐metamaterial waveguides exhibit the same measured quality factors, near 30 000. Having similar measured quality factors and better calculated bulk sensitivity than strip waveguides, the proposed dual‐metamaterial geometry stands as a promising approach to control modal confinement in silicon waveguides. Abstract : Controlling the modal confinement in silicon photonic waveguides is the key for applications in sensing and hybrid integration. A new strategy is proposed exploiting metamaterial engineering of the waveguide core and cladding to control the index contrast in the vertical and horizontal directions, independently. The proposed dual‐metamaterial geometry stands as a promising approach to control modal confinement in silicon waveguides.